Role of nurse in prevention of chosen complications connected with patient immobilization - Miller, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Hypokinesis refers to patients staying at hospital departments of many specializations. Because of limited possibilities of rehabilitation treatment by qualified physiotherapists for all patients who need it, the implementation of basic rehabilitation tasks by qualified nurse team in each hospital department is necessary. To remain in horizontal position is necessary in plenty of diseases however long period of immobilisation could be equally harmful. Limited physical activity is the cause of wrong physiologic and biochemic reaction. It whirls a lot of systems: circulation, nerves, muscles, bone and has influence on hydroelectrolic administration first of all calciphic and coagulability processes of blood. Remaining in horizontal position for a long time and lack of physical activity decreases total body metabolism leading to worse functional efficiency of all of the human systems, what leads to clinic symptoms of immobilization syndrome. The role of nurses (qualified in basic rehabilitation tasks) is very important because even short sessions of easy daily exercises like sitting up, using different positions can prevent patient’s organism from negative effects of hipokinesis. Breaking hipokinesis with short lasting physical exercises can increase recovery.